Staffing strategies in multinational enterprises - Kalugina, Daria; Brunet-Thornton, Richard; Martínez, Felipe; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2018)
This paper aims to create an integrated approach to global staffing, which develop the diverse perspectives on the key areas of global staffing and help to make connections among different topics. In theoretical part the author aims to identify models of staffing the MNE, traditional and alternative forms of global staffing and ways of composing the international staff, including international talent management, cross-cultural training and the position of women in management. The latest concepts and activities of global staffing are presented in the practical part of this paper and are discussed in relation to recent developments in international business, in order to help to relate the theoretical findings to what is currently happening in the real multinational enterprise.
Vedoucí práce: Richard Brunet-Thornton
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: podniková ekonomika a management [obor dipl. práce]; diplomové práce; master's theses